PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN APLIKASI KINEMASTER PADA MATERI HIDROKARBON DI SMAN 1 INUMAN - Anggraini, Reska Ayu; Yuhelman, Nofri; Ningsih, Jumriana Rahayu (Journal of Chemistry Education and Integration, 2022)
Abstract This research on the development of animated video media using the kinemaster application aims to deter- mine the feasibility of chemistry learning media on hydrocarbon materials for SMAN 1 Inuman. The data collection instruments used were material expert validation sheets, media expert validation sheets, lin- guist validation sheets and student response validation sheets. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the validation results met the valid categories of material experts by 91.93%, media experts by 90.00%, and linguists by 90.47%. This learning media also meets the valid category from the results of student responses with val- idation gains of 91.59%. Based on these results, it can be concluded that the animated video learning media is very suitable to be used as a medium for learning chemistry on hydrocarbon materials. Keywords: Learning Media, Animation Videos, Kinemaster, Hydrocarbons